2009
DOI: 10.1080/09735070.2009.11886342
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculin Skin Test (TST) Indurations in Smear Positive TB Patients and Healthy Individuals in Calabar, Nigeria

Abstract: The tuberculin skin test (TST) is used to detect latent Mycobacterium tuberculosis infection. WHO guidelines recommend 10mm as tuberculosis (TB) infection threshold for high risk individuals and 15mm for persons with no risk factors for TB. Nigeria is one of the 22 high burden countries for TB and her population is at risk of exposure to the TB germ. In an attempt to investigate indigenous TST indurations in a local population, 200 apparently healthy new students of tertiary institutions and other residents of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…It therefore suggests the extent of over-diagnosis of LBTI in studies that solely rely on TST results. Asuquo et al [21] reported a 45.8% prevalence among smear positive patients and healthy individuals using TST in Calabar, Nigeria. In IGRA, the level of IFN-ɣ produced by lymphocyte cells sensitized with antigens such as ESAT-6 and CFP-10, so measured, are significantly more specific to M. tuberculosis infection than PPD, and are not shared with BCG sub-strains or several nontubercular mycobacteria species that might cause non-specific sensitization [5].…”
Section: Discussionmentioning
confidence: 99%
“…It therefore suggests the extent of over-diagnosis of LBTI in studies that solely rely on TST results. Asuquo et al [21] reported a 45.8% prevalence among smear positive patients and healthy individuals using TST in Calabar, Nigeria. In IGRA, the level of IFN-ɣ produced by lymphocyte cells sensitized with antigens such as ESAT-6 and CFP-10, so measured, are significantly more specific to M. tuberculosis infection than PPD, and are not shared with BCG sub-strains or several nontubercular mycobacteria species that might cause non-specific sensitization [5].…”
Section: Discussionmentioning
confidence: 99%
“…There is high prevalence of HIV (5% cluster prevalence) in the eastern part of Nepal, though documented data is of 0.5%. 19 Nonetheless, whether or not a particularly infected person will become ill is impossible to predict with certainity. However, it has been estimated that 5% of infected persons get sick within 12-24 months of being infected; another 5% heal initially but, after years or decades, develop active TB either in the lungs or elsewhere in the body.…”
Section: Table 3: Sensitivity Specificity and Predictive Values Of Ts...mentioning
confidence: 99%
“…However, it has been estimated that 5% of infected persons get sick within 12-24 months of being infected; another 5% heal initially but, after years or decades, develop active TB either in the lungs or elsewhere in the body. 19 A significant proportion (27. The present study showed significant relationship between gender and size of induration. Males were more reactive than females.…”
Section: Table 3: Sensitivity Specificity and Predictive Values Of Ts...mentioning
confidence: 99%